2021
DOI: 10.1155/2021/8701180
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Deformation and Failure Characteristics of Anchor under Graded Loading and Corrosion

Abstract: During the entire life cycle of rock and soil anchors, owing to the influence of adverse factors such as the working environment, load change, and anchor performance degradation, the working load of the anchor will continue to increase and the mechanical properties will continue to deteriorate, which significantly affects the safety and stability of rock and soil anchors. Therefore, this study focuses on the deformation and failure characteristics of anchors under loading and corrosion conditions by means of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Wang Y. et al (2019) showed that the anchor head is relatively fragile through the collection and analysis of field samples. Sun et al (2021)demonstrated that shear failure occurs with the extension and evolution of cracks by means of laboratory simulation tests. As a main defect of the prestressed anchors, it is necessary to study the mechanism of prestressing loss (Gao et al, 2021).…”
Section: The Prestressed Anchorsmentioning
confidence: 99%
“…Wang Y. et al (2019) showed that the anchor head is relatively fragile through the collection and analysis of field samples. Sun et al (2021)demonstrated that shear failure occurs with the extension and evolution of cracks by means of laboratory simulation tests. As a main defect of the prestressed anchors, it is necessary to study the mechanism of prestressing loss (Gao et al, 2021).…”
Section: The Prestressed Anchorsmentioning
confidence: 99%
“…Zhao et al [12] studied the creep deformation characteristics of red sandstone under uniaxial compression and multi-stage loading. sun et al [13] studied the failure characteristics of anchors under multi-stage loading and corrosion by indoor test. Zheng et al [14] conducted a uniaxial compression test on fiber reinforced concrete, and discussed the influence of fiber type and fiber content on the uniaxial compressive strength of fiber reinforced concrete, showing nonuniformity and nonlinearity.…”
Section: Introductionmentioning
confidence: 99%